2021
DOI: 10.1111/radm.12468
|View full text |Cite
|
Sign up to set email alerts
|

Managing exploration persistency in ambidextrous organizations

Abstract: The concept of ambidextrous organization, which is allowing exploration and exploitation to coexist within an organization, has attracted considerable interest and is useful in understanding the corporate transformation process. We aim to advance the framework of ambidextrous organization by incorporating the aspect of exploration persistency. Our in-depth case study revealed the contrasting persistence of exploration for new technology and new business between Fujifilm and Kodak through analysis of patent dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…First, we propose a greater emphasis on directing more literature toward independent research on exploratory innovation rather than the ambidexterity perspective. Because of organizational inertia and current performance pressures (Atuahene-Gima, 2005; O'Reilly and Binns, 2019; Shibata et al , 2022), enterprises frequently face dilemmas resulting in the loss of exploratory innovation, which diminishes the proportion and share of exploratory innovation in practical implementation (Randall et al , 2017; Zhu et al , 2021). Although current research focuses on how to orchestrate and balance exploration and exploitation simultaneously (Ambroise et al , 2020; O’Reilly and Tushman, 2013; Turner et al , 2013; Tushman and O'Reilly, 1996), the issue of addressing loss and enhancing exploratory innovation remains neglected.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we propose a greater emphasis on directing more literature toward independent research on exploratory innovation rather than the ambidexterity perspective. Because of organizational inertia and current performance pressures (Atuahene-Gima, 2005; O'Reilly and Binns, 2019; Shibata et al , 2022), enterprises frequently face dilemmas resulting in the loss of exploratory innovation, which diminishes the proportion and share of exploratory innovation in practical implementation (Randall et al , 2017; Zhu et al , 2021). Although current research focuses on how to orchestrate and balance exploration and exploitation simultaneously (Ambroise et al , 2020; O’Reilly and Tushman, 2013; Turner et al , 2013; Tushman and O'Reilly, 1996), the issue of addressing loss and enhancing exploratory innovation remains neglected.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…However, this claim may not be valid in all cases. Taking Kodak as an example, although Kodak anticipated the decline of the traditional film business and explored new markets in medical care, optics, audio-visual equipment, IT and other technical fields, most new businesses failed because of a lack of persistence (Shibata et al , 2022). Another example is Siemens, which found it necessary to abandon its ingrained beliefs to reverse the continued decline in its market share in the molecular imaging market.…”
Section: Introductionmentioning
confidence: 99%
“…Fujifilm adopted the organizational initiative exploration processes that helped them narrow down from wider area of exploration and accumulate specific domain knowledge (by managers) which resulted in high degree of exploration persistency. Shibata, Baba, and Suzuki (2022, p. 22) defined it as “the degree to which an organization continues exploration in a consistent direction along a particular path and the amount of resources the organization applies to or invests in the exploration activity until the organization realizes that it is headed in the wrong direction.” On the other hand, Kodak adopted CEO initiative exploration process, which led to change in knowledge accumulation process depending on the CEO's decision of business exploration, which in turn resulted in lower exploration persistency (Shibata et al, 2022).…”
Section: Introduction and Extent Literaturementioning
confidence: 99%
“…They found that frontline managers play a more central, proactive, and strategic role with respect to organizational ambidexterity through configurational practices than assumed by senior executives' initial design choices. Another example illustrating the importance of the role of managers is the case study of Fujifilm and Kodak (Shibata, Baba, & Suzuki, 2022). Fujifilm adopted the organizational initiative exploration processes that helped them narrow down from wider area of exploration and accumulate specific domain knowledge (by managers) which resulted in high degree of exploration persistency.…”
mentioning
confidence: 99%
“…Companies need to survive in a VUCA environment, and Industry 4.0 can help them to be constant innovators by anticipating their customers' needs(Frank, Mendes et al, 2019;Shibata et al, 2021). Industry 4.0 fosters collaboration and can benefit the environment and society(Nascimento et al, 2019;Tao & Qi, 2019).…”
mentioning
confidence: 99%